Цивільний відповідач у кримінальному провадженні - Сорока, Світлана; Римарчук, Галина; Soroka, Svitlana; Rimarchuk, Galina; Сорока, Светлана; Римарчук, Галина (Видавництво Львівської політехніки, 2018)
Розглянуто питання, пов’язані із з’ясуванням деяких аспектів правового статусу цивільного відповідача як учасника (суб’єкта) кримінального провадження. Участь осіб у кримінальному провадженні потребує чіткого знання прав та обов’язків кожного учасника цих відносин, зокрема і цивільного відповідача. Визначено, що цивільний відповідач є самостійним учасником кримінального процесу, який відповідно до свого статусу має мати права та обов’язки, які мають бути безпосередньо визначені кримі- нальним процесуальним законодавством. Запропоновано зміни до чинного криміналь- ного процесуального законодавства.

The article deals with issues related to elucidation of some aspects of the legal status of a civil defendant as a participant (subject) of criminal proceedings. The participation of persons in criminal proceedings requires a clear knowledge of the rights and obligations of each participant in these relations, since within the framework of this proceeding activity is carried out which may result in bringing the person to criminal liability that will result in a certain restriction of his rights and freedoms. A person who is liable for compensation for damage in a criminal proceeding is a civil defendant who has the responsibility to be responsible for the claims brought by the plaintiff within the limits and in the circumstances determined by the procedural law. Thus, a civilian defendant as a party to a criminal proceeding is a person who is defending himself and being involved in answering a claim made by the plaintiff. It is determined that the civil defendant is an independent participant in the criminal process, who, according to his status, should have rights and obligations that must be directly determined criminal procedural law. Proposed changes to the existing criminal procedural legislation.

В статье рассмотрены вопросы, связанные с выяснением некоторых аспектов правового статуса гражданского ответчика как участника (субъекта) уголовного производства. Участие лиц в уголовном производстве требует четкого знания прав и обязанностей каждого учасника этих отношений, в том числе и гражданського ответчика. Определено, что гражданський ответчик является самостоятельным учасником уголовного процесса, согласно своему статусу обязан иметь права и обязанности, которые должны бать непосредственно определены уголовным процессуальным законодательством. Предложены изменения в действующем уголовном процессуальном законодательстве.
Civil responsible in criminal proceedings
Гражданский ответчик в уголовном производстве
Keywords: кримінальне провадження; цивільний відповідач; правовий статус; criminal proceedings; civil defendant; legal status; уголовное производство; гражданский ответчик; правовой статус; 343.1